Discussing the News : The Uneasy Alliance of Participatory Journalists and the Critical Public - Smith, Simon (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book examines two new roles that journalists assume in a participatory media environment - the administration (moderation) of online discussion and the monitoring of and engagement in comments below their articles. The author argues that it is precisely because both roles are treated as peripheral and undignified in newsrooms that they are so revealing, following the maxim: to make sense of what professions are and where they are heading, look at their boundaries and their dirty work. Based on a three-year ethnographic study, it offers key insights about the role of the media as democratic intermediaries in political participation, the creative possibilities for 'amateurs' as co-producers of digital news, the changing character of the knowledge professions and the dynamics of organisational innovation. The book argues that as media organisations face a crisis in their ability to represent the public, the challenge is to orchestrate participatory journalism as a collective accomplishment in which everyone is not a journalist but everyone can be a contributor. Bridging the divides between communication studies, linguistics, STS, organisational and occupational sociology it will interest social scientists and media studies experts.
Keywords: Social sciences.; Communication.; Social media.; Ethnography.; Mass media.; Social sciences in mass media.; Journalism.; Sociology.; elektronické knihy; electronic books